캡스톤 디자인 기반 예비보육교사의 현장연계 유아평가 실행연구 - 박미경(Mi-Kyung Park) (한국콘텐츠학회 논문지, 24(12), 2024)
본 연구는 코로나19 이후 현장연계 캡스톤 디자인의 유아평가 수업을 통하여 예비교사의 유아평가 전문성을 향상시키는데 있다. 이를 위해 경기도 국공립어린이집 교사 1명과 2022년 K대학교 캡스톤디자인 수업에 참여한 보육전공 3학년 25명이 참여하여 2022.8.1.-12.16간 4단계로 실행연구를 수행하였다. 실행연구의 결과를 논하면 첫째, 계획’ 단계에서는 현장의 문제점인 코로나19 이후 유아 발달을 평가하는 방법의 필요성에 대해 인식하고 현장교사와 함께 계획하였다. ‘1차 실행’ 단계에서는 아동발달검사도구(K-CDI)를 선정하여 3세 10명을 대상으로 검사 후 발달 평가자료를 제공하였다. ‘반성 후 재실행’ 단계에서는 교사로부터 피드백 받은 유아평가 결과와 해석을 보완하였으며, 평가 결과에 따른 발달영역별 놀이 교구 4종도 제작하였다. ‘평가’ 단계에서 유아와 평가에 대해 이해하게 되고, 교사로서 자신감도 가지게 되었다. 본 연구는 캡스톤 디자인을 기반으로 현장의 문제를 접하고 해결해 본 실행 경험은 예비교사들에게 전문성 함양의 기회가 제공된다는 시사점을 가지며, 향후 예비교사를 위한 캡스톤디자인 교과 운영이 활성화되기를 기대한다. The purpose of this study is to improve the expertise of prospective teachers in early childhood assessment through field-related capstone design early childhood assessment classes after COVID-19. For this purpose, one teacher from a public daycare center in Gyeonggi-do and 25 third-year child care majors who participated in the 2022 K University Capstone Design class participated and conducted an action research in four stages between August 1 and December 16, 2022. Discussing the results of the action research, first, in the 'planning' stage, the need for a method to evaluate children's development after COVID-19, which was a problem in the field, was recognized and planned together with field teachers. In the ‘first implementation’ stage, the Child Development Inspection Tool (K-CDI) was selected and development evaluation data were provided after the test to 10 3-year-olds. In the ‘re-execution after reflection’ stage, we supplemented the results and interpretations of the children’s evaluation received from teachers with feedback, and also produced four types of play materials for each development area based on the evaluation results. In the ‘evaluation’ stage, I gained an understanding of children and evaluation, and gained confidence as a teacher. This study has implications that the implementation experience of encountering and solving field problems based on capstone design provides opportunities for professional development to prospective teachers, and is expected to revitalize the operation of the capstone design curriculum for prospective teachers in the future. KCI Citation Count: 0